High-entropy alloy VCrMnFeAu nano material and application thereof in detection of miRNA-141
By preparing VCrMnFeAu0.5 high-entropy nanoalloy and target-induced DNA circulation electrochemical sensors, the problems of high cost, complex operation and limited stability in miRNA-141 detection are solved, and high sensitivity and selectivity are achieved, with lower detection limits and easier operation.
Patent Information
- Application Number
- CN202411839728.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art has problems such as high detection cost, complex operation, slow detection speed and limited stability in the detection of miRNA-141, making it difficult to achieve high sensitivity and low cost detection.
High entropy nano alloys with VCrMnFeAu0.5 were prepared by combining metal ions with coordination and high-temperature thermal annealing of arginine and folic acid-functionalized boron and phosphorus-doped graphene quantum dots (RFBP-GQDs), and miRNA-141 was detected based on this alloy and an electrochemical sensor that induces DNA circulation.
It achieves ultra-high sensitivity and selectivity, with a detection limit of 3.4×10-21M, which is easy to operate, does not require professional operation, and has better catalytic activity than traditional synthetic gold nanocrystals.
Smart Images

Figure CN119772193A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high entropy alloy VCrMnFeAu nano material and application thereof in detecting miRNA-141, belonging to the field of molecular biology detection. Background Art
[0002] miRNA-141 is a microRNA molecule that is widely present in organisms. It plays an important role in regulating cell growth, differentiation, and various physiological and pathological processes. However, recent studies have found that abnormal expression of miRNA-141 is closely related to the occurrence and development of various diseases, including cancer, cardiovascular disease, and urinary system diseases. The occurrence of these diseases is often accompanied by significant changes in the expression level of miRNA-141. Therefore, finding a reliable method to detect the level of miRNA-141 in body fluids or tissues is of great significance for the early diagnosis, treatment monitoring, and prognosis evaluation of the disease.
[0003] The analytical detection technology for miRNA-141 is also constantly developing and improving, mainly including real-time fluorescence quantitative PCR, surface enhanced Raman spectroscopy (SERS), spectrophotometry and electrochemical sensors. Among them, real-time fluorescence quantitative PCR has high sensitivity and specificity, but it may also be affected by many factors such as sample processing, primer design and experimental conditions. SERS has ultra-high sensitivity and can even achieve single-molecule detection without fluorescent or chemical labeling of miRNA, but the instability of this method may limit its practical application. Spectrophotometry is usually not the preferred method for miRNA-141 detection because its sensitivity and specificity may not be as good as the other methods mentioned above.
[0004] Electrochemical sensors have become a powerful analytical technology in fields such as disease detection and environmental monitoring due to their advantages such as good portability, easy functionalization, high cost-effectiveness, and high selectivity. In electrochemical sensors, the rational design of advanced nanomaterials is crucial to establish signal amplification strategies for ultrasensitive electrochemical biosensing. Gold nanocrystals have become the main sensing material due to their excellent conductivity, catalytic ability, and the ease of immobilizing biomolecules using Au-S bonds, but the stability of gold nanocrystals decreases with their aggregation and oxidation. High entropy alloys (HEAs) are usually composed of five or more metal elements and have high configurational entropy, which helps to reduce the Gibbs free energy and thus improve their structural stability. Compared with gold nanomaterials, high entropy alloys have higher catalytic activity, chemical stability, and sensing performance, can accelerate the electrochemical reaction rate, and produce higher sensitivity.
[0005] Since miRNA has short sequences, high similarity and low content in actual samples, accurate detection and quantitative analysis of it are quite challenging. Signal amplification strategies can achieve high-precision detection, among which enzyme-free dynamic DNA self-assembly amplification technology (such as catalytic hairpin assembly CHA and hybridization chain reaction HCR) has been applied to a variety of biosensors to achieve signal amplification. When the target miRNA-141 is present, signal amplification strategies such as catalytic hairpin self-assembly (CHA) are triggered to achieve effective signal amplification and then convert it into an electrochemical signal. Therefore, by constructing a suitable target conversion biosensor, miRNA that is difficult to analyze directly can be converted into an output DNA signal that is easy to detect, while achieving significant signal amplification. The paper “Signal-on low background electrochemiluminescence biosensor based on the target-triggered dual signal amplifications and difference of electrostatic attraction;DOI:10.1016 / j.snb.2022.133035” discloses a method in which miRNA-141 can trigger an enzyme-free isothermal catalytic hairpin self-assembly (CHA) and hybrid chain reaction (HCR) cascade reaction to generate an electrochemiluminescence signal. The detection limit of miRNA-141 is 1.7×10 -16 M; The literature “Target “turn on” electrochemical pseudocapacitive sensor for ultrasensitive detection of microRNA-141; DOI: 10.1016 / j.snb.2023.133469” discloses the detection of miRNA-141 based on gold nanoparticles and nitrogen-doped carbon nanotubes, with a detection limit of 4.4×10 -17 The above technologies have problems such as high detection cost, complex operation, slow detection speed, and limited stability.
[0006] It can be seen that it is still challenging to construct a high-performance biosensor for electrochemical detection of miRNA-141. Therefore, it is urgent to develop a highly sensitive, low-cost, and selective biosensor with high practical value. Summary of the invention
[0007] [Technical issues]
[0008] Prepare materials with higher catalytic activity, chemical stability and sensing performance, and improve the stability of materials due to aggregation and oxidation.
[0009] In actual samples, miRNA-141 has a short sequence, high similarity and low content. The sensitivity of the sensor is improved by adding DNA circular amplification.
[0010] [Technical solution]
[0011] To solve the above problems, the present invention combines the coordination of metal ions with arginine and folic acid functionalized boron and phosphorus doped graphene quantum dots (RFBP-GQD) and high temperature thermal annealing to prepare VCrMnFeAu 0.5 The high entropy nano alloy has high stability and sensing performance. 0.5 The electrochemical aptamer sensor with target-induced DNA recycling detected miRNA-141 and exhibited ultra-high sensitivity and selectivity.
[0012] A first object of the present invention is to provide a high entropy alloy, wherein the preparation method of the high entropy alloy comprises:
[0013] (1) mixing NH4VO3, MnCl2, FeCl3, CrCl3 and HAuCl4 in a molar ratio of 1-2:1-2:1-2:1-2:0.2-0.8 and dissolving in water to obtain a metal salt solution;
[0014] (2) Mixing the arginine and folic acid functionalized boron and phosphorus doped graphene quantum dots (RFBP-GQD) solution with the metal salt solution to obtain a mixed solution
[0015] (3) The mixed solution is dried and thermally annealed to obtain a high entropy alloy.
[0016] In one embodiment, the total concentration of the metal salt in the metal salt solution in step (1) is 1 to 4 mmol / L.
[0017] Optionally, the total concentration of the metal salt in the metal salt solution is 2 to 3 mmol / L; preferably, the total concentration of the metal salt in the metal salt solution is 2.7 to 2.9 mmol / L.
[0018] In one embodiment, the mass ratio of the total mass of metal salts (i.e., the total mass of NH4VO3, MnCl2, FeCl3, CrCl3 and HAuCl4) in the mixed solution of step (3) to the mass ratio of arginine and folic acid functionalized boron and phosphorus doped graphene quantum dots (RFBP-GQD) is 1:1.2 to 1.8.
[0019] Optionally, the mass ratio of the total mass of the metal salt to the mass ratio of RFBP-GQD is 1:1.4 to 1.6; preferably, the mass ratio is 1:1.5.
[0020] In one embodiment, thermal annealing includes two stages. The first stage is 1-5°C / min, heating to 380-420°C; the second stage is 5-8°C / min, heating to 880-920°C, and keeping warm for 2-3h.
[0021] Preferably, the heating is performed to 400° C. in the first stage and to 900° C. in the second stage.
[0022] In one embodiment, the preparation method of RFBP-GQD comprises:
[0023] Dissolve citric acid, arginine, folic acid and boric acid in phosphoric acid according to a mass ratio of 1-3:1-2.7:0.063-1:0.7-1.3; heat at 150-180°C for 3-4h to obtain crude graphene quantum dots functionalized with arginine and folic acid and doped with boron and phosphorus; redissolve, dialyze and freeze-dry the crude product to obtain graphene quantum dots functionalized with arginine and folic acid and doped with boron and phosphorus;
[0024] Optionally, the usage ratio of citric acid to phosphoric acid is 1-3 g: 0.2-0.4 mL.
[0025] In one embodiment, the preparation method of RFBP-GQD is:
[0026] Under stirring conditions, 1-3 g of citric acid, 1-2.7 g of arginine, 0.063-1 g of folic acid, 0.7-1.3 g of boric acid, and 200-315 μL of 85% phosphoric acid were mixed. The resulting mixture was transferred to a high-temperature oven and then heated at 150-180 °C for 3-4 hours. The collected crude RFBP-GQDs were dissolved in ultrapure water to produce 40-50 mg mL -1 The large graphene flakes were removed by filtration, the unreacted raw materials were removed by dialysis with 2500-3000Da, and then the solid RFBP-GQD product was obtained by freeze drying.
[0027] In one embodiment, the high entropy nanoalloy (VCrMnFeAu 0.5 ), the steps are as follows:
[0028] (1) Weigh 0.5-0.7 mmol NH4VO3, 0.5-0.7 mmol MnCl2, 0.5-0.7 mmol FeCl3, 0.5-0.7 mmol CrCl3 and 0.3-0.5 mmol HAuCl4 and dissolve them in 10-15 mL deionized water and stir for 20-50 min;
[0029] (2) Weigh 1 to 2 times the total mass of the metal salt and dissolve RFBP-GQD in 60 mL of deionized water. Adjust the pH to 7 and then add the metal salt solution and stir for 3 to 5 hours.
[0030] (3) After the reaction is completed, the liquid is poured into a watch glass and dried in a vacuum oven at 50-60°C to obtain a solid product. The collected metal complex is thermally annealed in a N2 atmosphere to generate VCrMnFeAu 0.5 ;
[0031] The thermal annealing includes two stages. The first stage includes a heating rate of 1 to 5 °C / min and a temperature of 400 °C. The second stage includes a heating rate of 5 to 8 °C / min, a temperature of 900 °C, and a holding time of 2 to 3 hours. After the thermal annealing, the temperature is lowered and collected after the temperature drops to room temperature to prepare VCrMnFeAu 0.5 High entropy nanoalloys.
[0032] The second object of the present invention is to provide a biosensor for detecting miRNA141, wherein the preparation method of the biosensor comprises:
[0033] The high entropy alloy and chitosan are mixed and added to the electrode surface to obtain a modified electrode; the H1 DNA solution is heated until the H1 DNA forms a hairpin structure to obtain a pretreated H1 solution; the pretreated H1 solution is mixed with a TCEP aqueous solution, added to the modified electrode surface, and incubated; mercaptoethanol is added to the electrode surface and incubated to obtain a biosensor for detecting miRNA141;
[0034] Wherein, the preparation method of the high entropy alloy comprises:
[0035] (1) ammonium metavanadate NH4VO3, manganese chloride MnCl2, ferric chloride FeCl3, chromium chloride CrCl3 and chloroauric acid HAuCl4 are mixed in a molar ratio of 1-2:1-2:1-2:1-2:0.2-0.8 and dissolved in water to obtain a metal salt solution;
[0036] (2) mixing the arginine and folic acid functionalized boron and phosphorus doped graphene quantum dots solution with the metal salt solution to obtain a mixed solution; wherein the mass ratio of the total mass of the metal salt to the arginine and folic acid functionalized boron and phosphorus doped graphene quantum dots is 1:1.2-1.8;
[0037] (3) The mixed solution is dried and thermally annealed to obtain a high entropy alloy.
[0038] In one embodiment, the H1 DNA has a methylene-thiol group attached to the 3' end of the nucleotide sequence shown in SEQ ID NO. 1, that is:
[0039] 5'-CCGAGATTCCAATGCCATAGTGTCTTCCAAGTTCAGATCTCAGACACTGTCTGGGTGTAAAGATGGGGACAGAATACAATAAG-(CH2)6-SH-3'.
[0040] In one embodiment, the concentration of the H1 DNA solution is 1-5 μM.
[0041] In one embodiment, the mass ratio of high entropy alloy to chitosan is 5-2:1-3.
[0042] In one embodiment, the concentration of the metal salt solution in step (1) is 1 to 4 mmol / L.
[0043] Optionally, the concentration of the metal salt solution is 2-3 mmol / L; preferably, the concentration of the metal salt solution is 2.7-2.9 mmol / L.
[0044] In one embodiment, the mass ratio of the total mass of metal salts (i.e., the total mass of NH4VO3, MnCl2, FeCl3, CrCl3 and HAuCl4) in the mixed solution of step (3) to the mass ratio of arginine and folic acid functionalized boron and phosphorus doped graphene quantum dots (RFBP-GQD) is 1:1.2 to 1.8.
[0045] Optionally, the mass ratio of the total mass of the metal salt to the mass ratio of RFBP-GQD is 1:1.4 to 1.6; preferably, the mass ratio is 1:1.5.
[0046] In one embodiment, the method for preparing the sensor comprises the following steps:
[0047] (1) VCrMnFeAu 0.5 and chitosan in a mass ratio of 5-2:1-3, and 3-6 μL is dropped on the glassy carbon electrode;
[0048] (2) The H1 solution was heated in a water bath at 90-95°C for 4-6 minutes and then cooled to room temperature to form a hairpin structure;
[0049] (3) Mix the pretreated H1 (3-5 μL, 8-10 μM) and TCEP (14-20 μL, 1-2 mM) aqueous solutions, incubate at room temperature for 20-30 min, take 3-6 μL and drop it on the modified electrode, incubate at 35-37 °C for 1-2 h, then drop 2-4 μL of 1-2 mM mercaptoethanol (MCH) on the surface to block other surface active sites, and incubate at 35-37 °C for 0.5-1.5 h.
[0050] In one embodiment, H1 is connected to a methylene-thiol group at the 3' end of the nucleotide sequence of SEQ ID NO.1, that is:
[0051] 5'-CCGAGATTCCAATGCCATAGTGTCTTCCAAGTTCAGATCTCAGACACTGTCTGGGTGTAAAGATGGGGACAGAATACAATAAG-(CH2)6-SH-3'.
[0052] The third object of the present invention is to provide a use of any of the above-mentioned high entropy alloys or any of the above-mentioned biosensors in the preparation of miRNA141 detection products;
[0053] Optionally, the detection product includes a detection probe, a detection kit, and a detection device.
[0054] The fourth object of the present invention is to provide a kit for detecting miRNA141, the kit comprising any of the above-mentioned biosensors, H2 DNA, and H3 DNA;
[0055] Among them, H2 DNA is shown in SEQ ID NO.2.
[0056] In one embodiment, H3 DNA is a ferrocene-modified hairpin DNA, and ferrocene FC is connected to the 5' end of the nucleotide sequence shown in SEQ ID NO.3, that is:
[0057] 5'-FC-TCCTTGTTCTCATCTGAGCCATAGATTACACCCAGACAGTGTCTGAGATCTGAACTTGGAAGACAC-3'.
[0058] A fifth object of the present invention is to provide a method for detecting miRNA141, using any of the above-mentioned biosensors or the above-mentioned kits, the detection method comprising:
[0059] The H2 DNA solution and the H3 DNA solution are heated separately until a hairpin structure is formed; the H2 DNA solution and the sample to be tested are mixed and incubated to obtain a mixed solution; the mixed solution is mixed with the H3 DNA solution and a buffer solution to obtain a test solution, which is added to the surface of the biosensor and incubated; after incubation, the DPV curve is detected to obtain a peak current; the peak current is brought into the standard curve to calculate the concentration of miRNA-141;
[0060] The standard curve is: Ip(nA)=48.5×LOG[C miRNA-141 , M]+977.3; where Ip is the peak current, nA; CmiRNA-141 is the concentration of miRNA141, M;
[0061] Optionally, heating the H2 DNA solution and the H3 DNA solution to form a hairpin structure is performed by heating in a water bath at 90 to 95° C. for 4 to 6 minutes and cooling to room temperature;
[0062] Optionally, the volume ratio of the H2 DNA solution to the sample to be tested is 8-10:40; 8-10;
[0063] Optionally, 3 to 6 μL of the test solution is added to the surface of the biosensor;
[0064] Optionally, the test solution is added to the biosensor surface and incubated at 35-37° C. for 1.5-2 h;
[0065] Optionally, the concentration of the H2 DNA solution and the H3 DNA solution is 8-12 μM.
[0066] In one embodiment, the sample to be tested may be a serum sample.
[0067] In one embodiment, the buffer is a TE mixture.
[0068] In one embodiment, a method for electrochemically detecting miRNA-141 comprises the following steps:
[0069] (1) H2 and H3 solutions were heated in a water bath at 90-95°C for 4-6 min and then cooled to room temperature to form a hairpin structure;
[0070] (2) 8-10 μL H2 and 40 μL sample were mixed and incubated in a 35-37°C water bath for 20-30 min to obtain a mixed solution;
[0071] (3) Take 15-20 μL of the mixed solution, mix it with 15-20 μL of H3 dispersion and 8-10 μL of TE buffer solution, vortex and take 3-6 μL to drop on the sensor surface, incubate at 35-37°C for 1.5-2 h, measure the DPV curve in 0.1-0.2 mM PBS with a pH of 7.0-7.4, and obtain the peak current;
[0072] (3) Bring the peak current into the standard curve Ip (nA) = 48.5 × LOG [C miRNA-141 , M]+977.3, and the miRNA-141 concentration was calculated.
[0073] In one embodiment, the concentration of the H2 DNA solution is 8-12 μM; the concentration of the H3 DNA solution is 8-12 μM.
[0074] The sixth object of the present invention is to provide a method for improving the detection accuracy of miRNA141, using the kit described in claim 8, the detection method comprising:
[0075] Using any of the above biosensors or the above kits, the detection method comprises:
[0076] The H2 DNA solution and the H3 DNA solution are heated separately until a hairpin structure is formed; the H2 DNA solution and the sample to be tested are mixed and incubated to obtain a mixed solution; the mixed solution is mixed with the H3 DNA solution and the TE buffer solution to obtain a test solution, which is added to the surface of the biosensor and incubated; after incubation, the DPV curve is detected to obtain a peak current; the peak current is brought into the standard curve to calculate the miRNA-141 concentration;
[0077] The standard curve is: Ip(nA)=48.5×LOG[C miRNA-141 , M]+977.3; where Ip is the peak current, nA; CmiRNA-141 is the concentration of miRNA141, M;
[0078] Optionally, heating the H2 DNA solution and the H3 DNA solution to form a hairpin structure is performed by heating in a water bath at 90 to 95° C. for 4 to 6 minutes and cooling to room temperature;
[0079] Optionally, the volume ratio of the H2 DNA solution to the sample to be tested is 8-10:40; 8-10;
[0080] Optionally, 3 to 6 μL of the test solution is added to the surface of the biosensor;
[0081] Optionally, the test solution is added to the biosensor surface and incubated at 35-37° C. for 1.5-2 h;
[0082] Optionally, the concentration of the H2 DNA solution and the H3 DNA solution is 8-12 μM.
[0083] [Beneficial Effects]
[0084] The present invention combines the coordination of metal ions with arginine and folic acid functionalized boron and phosphorus doped graphene quantum dots (RFBP-GQD) and high temperature thermal annealing to prepare VCrMnFeAu 0.5 The high entropy nano alloy has high stability and sensing performance. 0.5 The electrochemical aptamer sensor with target-induced DNA recycling detected miRNA-141 and exhibited ultra-high sensitivity and selectivity.
[0085] Specifically:
[0086] (1) The detection limit (LOD) of the detection method of the present invention reaches 3.4×10 -21 M, detection range is 1×10 -15 M~1×10-20 M, lower detection limit and higher sensitivity compared with other methods;
[0087] (2) Compared with the existing miRNA-141 detection method, the detection method of the present invention is simpler to operate and does not require professional personnel to operate;
[0088] (3) The present invention uses the coordination of metal ions with arginine and folic acid functionalized boron and phosphorus doped graphene quantum dots (RFBP-GQD) combined with high temperature thermal annealing to prepare VCrMnFeAu 0.5 High entropy nano alloys with simpler preparation methods;
[0089] (4) Compared with traditional synthetic gold nanocrystals, VCrMnFeAu 0.5 The high entropy nanoalloy has better catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0090] Figure 1 VCrMnFeAu 0.5 Field emission scanning electron microscopy image.
[0091] Figure 2 VCrMnFeAu 0.5 The catalytic performance of the components with different gold contents is compared. Figure 2 a, b, c, and d are VCrMnFeAu 0.5 、VCrMnFeAu 0.4 、VCrMnFeAu 0.3 and RFBP-GQD thermally reduced Au; Figure 2 A is their cyclic voltammetry curves (CV curves) in 1 mM potassium ferrocyanide solution, Figure 2 B is the scan rate versus current density plot of the CV calculated at different scan rates in 1 mM sodium chloride solution, and the slope represents the electrochemical active area.
[0092] Figure 3 The electrochemical behaviors of different modified electrodes are shown in Figure 2. Figure 3 A is the CV curve, Figure 3 B is the impedance (EIS) curve, where a is the CV and impedance (EIS) of the glassy carbon electrode (GCE) in a 1 mM potassium ferrocyanide solution prepared in PBS at pH = 7; b is the VCrMnFeAu 0.5 The chitosan was immobilized on the glassy carbon electrode (i.e., VCrMnFeAu 0.5 CV and EIS of H1 connected to VCrMnFeAu / GCE in 1 mM potassium ferrocyanide solution in PBS at pH = 7; c is the CV and EIS of H1 connected to VCrMnFeAu 0.5 On (ie, H1 / VCrMnFeAu 0.5 / GCE) in 1 mM potassium ferrocyanide solution in PBS at pH = 7; d is the CV and EIS of MCH-terminated (i.e., MCH / H1 / VCrMnFeAu 0.5 a) CV and EIS of DNA cycling in 1 mM potassium ferricyanide solution in PBS at pH = 7; e and f are CV and EIS of DNA cycling in 1 mM potassium ferricyanide solution in PBS at pH = 7 in the absence and presence of miRNA-141, respectively.
[0093] Figure 4 The differential pulse voltammetry (DPV) curve and linear diagram of electrochemical detection of miRNA-141 are shown in Figure 2. Figure 4 A shows the DPV curves of different concentrations of miRNA-141; Figure 4 B shows the logarithmic curve of Ip value and miRNA-141 concentration. DETAILED DESCRIPTION
[0094] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.
[0095] Test method:
[0096] 1. Electrochemical detection of miRNA-141
[0097] First, VCrMnFeAu 0.5 and 1% chitosan were added dropwise to the surface of glassy carbon electrode (GCE) to form VCrMnFeAu 0.5 / GCE; then the hairpin DNA H1 is fixed to VCrMnFeAu via Au-S bonds 0.5 / GCE surface, forming H1 / VCrMnFeAu 0.5 / GCE; then, mercaptoethanol (MCH) was fixed on H1 / VCrMnFeAu 0.5 / GCE surface to block the remaining active sites; finally, MCH / H1 / VCrMnFeAu 0.5 / GCE was incubated in a detection solution containing miRNA-141, H2, and H3 at 37°C for 30 min and washed with phosphate buffered saline (PBS) at pH 7.0. Differential pulse voltammetry (DPV) curves were measured in a PBS solution containing 1 mM pH 7.0. 0.5 / GCE、H1 / VCrMnFeAu 0.5 / GCE、MCH / H1 / VCrMnFeAu 0.5 / GCE means combination with each other; unless otherwise specified, “ / ” or “-” means connection or combination.
[0098] 2. Electrochemical measurement
[0099] Cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and differential pulse voltammetry (DPV) were measured on a CHI660D electrochemical workstation. All electrochemical measurements used a traditional three-electrode test system, with the sensor, Ag / AgCl electrode, and platinum wire used as the working electrode, reference electrode, and counter electrode, respectively. The frequency range of EIS measurement was 100 kHz to 1 Hz, the potential amplitude was ±5 mV, and the parameters of DPV were set to a scan rate of 4 mV s -1 , pulse amplitude was 50mV, pulse width was 20ms, and initial potential was -0.2V.
[0100] The raw materials used in the embodiment:
[0101] Chloroauric acid (HAuCl4), tris(2-carboxyethyl)phosphine hydrochloride (TCEP), mercaptohexanol (MCH) and K4Fe(CN)6 (>99.95%) were purchased from Sigma-Aldrich. Ammonium metavanadate (NH4VO3), manganese chloride (MnCl2), ferric chloride (FeCl3) and chromium chloride (CrCl3) were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0102] Hairpin DNAH1: A methylene-thiol group is connected to the 3' end of 5'-CCGAGATTCCAATGCCATAGTGTCTTCCAAGTTCAGATCTCAGACACTGTCTGGGTGTAAAGATGGGGACAGAATACAATAAG-3' (SEQ ID NO. 1), that is: 5'-CCGAGATTCCAATGCCATAGTGTCTTCCAAGTTCAGATCTCAGACACTGTCTGGGTGTAAAGATGGGGACAGAATACAATAAG-(CH2)6-SH-3';
[0103] Hairpin DNA H2: 5'-TGTCCCCCATCTTTACACCCAGACAGTGTTATTTTTTTTTTTTTTTTTTTTTTTTTTTTTTTTTTTTTTTTTTCTGTCCCCATCTTTACACCCAGACAGTTTGCG-3' (SEQ ID NO. 2);
[0104] Hairpin DNAH3: ferrocene (FC) is linked to the 5′ end of 5′-TCCTTGTTCTCATCTGAGCCATAGATTACACCCAGACAGTGTCTGAGATCTGAACTTGGAAGACAC-3′ (SEQ ID NO. 3), i.e.: 5′-FC-TCCTTGTTCTCATCTGAGCCATAGATTACACCCAGACAGTGTCTGAGATCTGAACTTGGAAGACAC-3′;
[0105] Short-chain RNA miRNA-141: 5'-UAACACUGUCUGGUAAAGAUGG-3' (SEQ ID NO. 4). All of the above were synthesized and purified by Shanghai Sangon Biotechnology Co., Ltd. Deionized water (DI water) was produced by Millipore Milli-Q grade with a resistivity of 18.2 MΩ·cm-1; other materials and reagents used were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0106] Ferrocene DNAH3: synthesized and purified by Shanghai Sangon Biotechnology Co., Ltd.;
[0107] RFBP-GQD preparation method:
[0108] RFBP-GQDs were prepared by heat treatment of arginine, folic acid, boric acid, and phosphoric acid as follows:
[0109] Under stirring conditions, 3 g of citric acid, 2.7 g of arginine, 0.063 g of folic acid, 0.7 g of boric acid, and 315 μL of 85% phosphoric acid were mixed; the resulting mixture was transferred to a high-temperature oven and heated at 180 °C for 3 h to obtain a crude RFBP-GQD product; the collected crude RFBP-GQD product was dissolved in ultrapure water to obtain 50 mg mL -1 The RFBP-GQD aqueous solution was prepared; large graphene flakes were removed by filtration, unreacted raw materials were removed by dialysis with 3000Da, and then solid RFBP-GQDs were obtained by freeze drying.
[0110] Example 1: High Entropy Nanoalloy (VCrMnFeAu 0.5 )
[0111] High entropy nano alloy (VCrMnFeAu 0.5 ), the steps are as follows:
[0112] (1) Weigh 0.64 mmol NH4VO3, 0.64 mmol MnCl2, 0.64 mmol FeCl3, 0.64 mmol CrCl3 and 0.32 mmol HAuCl4 and dissolve them in 10 mL deionized water and stir (180 rpm / min) for 30 min to obtain a metal salt solution;
[0113] (2) Weigh 1.5 times the total mass of the above metal salt RFBP-GQD and dissolve it in 60 mL of deionized water. After adjusting the pH to 7, add the metal salt solution and stir (180 rpm / min) for 3 h to obtain a mixed solution.
[0114] (3) The mixed solution was poured into a watch glass and dried in a vacuum drying oven at 50°C (24 h) to obtain a metal complex; the collected metal complex was thermally annealed in a N2 atmosphere; after thermal annealing, the temperature was cooled to room temperature to obtain a high entropy alloy, named VCrMnFeAu 0.5 ;
[0115] The thermal annealing includes two stages: the first stage is: heating at a rate of 1°C / min, heating to a temperature of 400°C; the second stage is: heating at a rate of 5°C / min, a temperature of 900°C, and a holding time of 2 hours.
[0116] The morphology of high entropy nanoalloys was observed using field emission scanning electron microscopy. Figure 1 As shown. SEM images show that VCrMnFeAu 0.5 The nanostructure has a cone-like shape, which achieves high electron conductivity and large specific surface area.
[0117] Comparative Example 1: VCrMnFeAu with different gold content
[0118] On the basis of Example 1, the amount of HAuCl4 in step (1) was changed to 0.256 mmol and 0.192 mmol, respectively, to prepare VCrMnFeAu 0.4 、VCrMnFeAu 0.3 , measure its CV curve and calculate the surface active area, the results are as follows Figure 2 shown.
[0119] Figure 2 A and Figure 2 The CV current and surface active area of the high entropy nanoalloy material with 0.5 component Au shown in B are the highest. After reducing the gold composition, the CV current and surface active area continue to decrease; Figure 2 The CV currents of abc in A are all larger than d. Figure 2The slope in B represents the double-layer capacitance Cdl measured by CV; when the specific capacitance is the same, the larger the Cdl, the larger the electrochemical active area ECSA. Figure 2 The slopes of abc in B are all greater than d, so the electrochemical active areas of abc are all greater than d. It can be seen that the high-entropy nanoalloy material prepared by combining the coordination of metal ions with arginine and folic acid functionalized boron and phosphorus doped graphene quantum dots (RFBP-GQD) and high-temperature thermal annealing has a higher CV current and a larger active area than the Au thermally reduced RFBP-GQD, and has better catalytic activity.
[0120] Example 2: Preparation of electrochemical sensor and detection of DNA circulation feasibility
[0121] Take the high entropy alloy VCrMnFeAu prepared in Example 1 0.5 , detecting its application in electrochemical sensors.
[0122] 1. The preparation method of the electrochemical sensor is as follows:
[0123] (1) 5 mg / mL VCrMnFeAu 0.5 and 10 mg / mL chitosan at a volume ratio of 5:1 to obtain a mixed solution, and 5 μL of the mixed solution was dropped on the glassy carbon electrode;
[0124] (2) pre-treated (H1 was heated in a water bath at 95°C for 5 min and then cooled to room temperature to form a hairpin structure) H1 (5 μL, 10 μM) and TCEP (20 μL, 1 mM) aqueous solutions were mixed and incubated at room temperature for 30 min to obtain H1 solution;
[0125] (3) 5 μL of H1 solution was dropped on the modified electrode and incubated at 37°C for 1 h. Then 4 μL of 1 mM mercaptoethanol (MCH) was dropped on the surface to block other surface active sites and incubated at 37°C for 0.5 h to obtain the sensor.
[0126] (4) The sensor and the H3 redox probe together form an electrochemical sensor.
[0127] 2. Electrochemical sensor DNA circulation feasibility test
[0128] Take the electrochemical sensor prepared in step 1 and drop 5 μL VCrMnFeAu on the electrodes of the electrochemical sensor. 0.5 The CV curves and EIS curves of the mixed solution, H1 (5 μL, 10 μM), 5 μL 1 mM mercaptoethanol (MCH), the mixed solution of H2 and H3 in the presence of miRNA-141, and the mixed solution of H2 and H3 in the absence of miRNA-141 were detected. The results are shown in Figure 3 shown.
[0129] Figure 3 It shows that there is a pair of redox peaks in all CV curves, which verifies that Fe(CN)6 4- Redox can be performed on all electrode surfaces; a relatively low CV current appears in the CV curve of the glassy carbon electrode (GCE) with a relatively large charge transfer resistance (Rct), which is due to the low conductivity of the GCE; VCrMnFeAu 0.5 After the addition of VCrMnFeAu, the CV current increased significantly with the decrease of Rct. This is because 0.5 The conductivity of MCH / H1 / VCrMnFeAu is high; the immobilization of H1 causes the CV current to decrease with the increase of Rct. Due to the electrochemical inertness, the presence of H1 will block some electron transfer channels, which reduces the electronic conductivity and causes the CV current to decrease with the increase of Rct. For the same reason, the immobilization of MCH greatly reduces the CV current and Rct increases significantly; but MCH / H1 / VCrMnFeAu 0.5 / GCE contains 1.0×10 -15 The CV current generated by the mixed solution of M miRNA-141, H2, and H3 increased significantly, while Rct decreased. This is because the presence of miRNA-141 triggers the target-induced DNA loop, through which one miRNA-141 molecule transfers many H3 ferrocene redox probes from the detection solution to the aptamer sensor surface. 0.5 It has excellent conductivity, and its introduction improves the conductivity of the modified layer. This accelerates the oxidation and reduction of K4Fe(CN)6 and brings about an increase in CV current. In addition, due to VCrMnFeAu 0.5 The high catalytic activity of K4Fe(CN)6 will further enhance the CV current.
[0130] Therefore, this electrochemical sensor can be used to detect miRNA-141.
[0131] Example 3: Application of electrochemical sensor in detecting miRNA-141
[0132] 1. Standard curve of miRNA-141 concentration corresponding to current peak and detection limit determination
[0133] Take the electrochemical sensor prepared in Example 2 to prepare a miRNA-141 content detection standard curve, the steps are as follows:
[0134] (1) 10 μL H2 (SEQ ID NO. 2) was mixed with 40 μL of 1×10 -15 M~1×10 -20M of miRNA-141 (SEQ ID NO. 4), and incubated in a 37°C water bath for 30 min to obtain a mixture of different miRNA-141 concentrations;
[0135] (2) Take 20 μL of the mixed solution with different miRNA-141 concentrations, mix it with 20 μL of H3 dispersion and 10 μL of TE buffer solution, vortex and drop 5 μL on the sensor surface, incubate at 37°C for 1 h, measure the DPV curve in 0.1 mM PBS with a pH of 7.4, obtain the peak current, and calculate the linear relationship between the peak current (Ip value) and the miRNA-141 concentration.
[0136] The results are as follows Figure 4 As shown in A, the results show that Ip increases with the increase of miRNA-141 concentration, and a relationship curve is drawn between the Ip value and the logarithm of miRNA-141 concentration; Figure 4 B shows that when miRNA-141 was expressed at 1×10 -15 M~1×10 -20 When the concentration of miRNA-141 was within the range of 1.5-2.0, Ip(nA) increased linearly with the increase of the logarithmic value of miRNA-141 concentration, and the linear regression equation was:
[0137] Ip(nA)=48.5×LOG[C miRNA-141 , M]+977.3, correlation coefficient (R 2 ) was 0.991, and the detection limit (LOD) reached 3.4×10 -21 M(S / N=3).
[0138] 2. Electrochemical detection of miRNA-141
[0139] A method for electrochemical detection of miRNA-141, comprising the following steps:
[0140] (1) Mix 10 μL H2 (10 μM) with 40 μL sample and incubate in a 37°C water bath for 30 min to obtain a mixed solution;
[0141] (2) Take 20 μL of the mixture, mix it with 20 μL of redox probe dispersion (i.e., H3 DNA, 10 μM) and 10 μL of TE buffer solution, vortex and drop 5 μL on the sensor surface, incubate at 37°C for 1 h, measure the DPV curve in 0.1 mM PBS with a pH of 7.4, and obtain the peak current;
[0142] (3) Bring the peak current into the standard curve Ip (nA) = 48.5 × LOG [C miRNA-141 , M]+977.3, and the concentration of miRNA-141 in the sample was calculated.
[0143] 3. Comparison of different miRNA-141 detection methods
[0144] “2. Electrochemical detection method of miRNA-141” was compared with the common methods for miRNA-141 detection, and the results are shown in Table 1.
[0145] Table 1 Different miRNA-141 detection methods
[0146]
[0147]
[0148] Table 1 is a comparison of the linear range and detection limit of the present method with the published methods. It can be seen that compared with the published miRNA-141 detection method, the miRNA-141 detection method of the present invention has a lower detection limit and is more sensitive.
[0149] Example 4: A miRNA-141 detection kit
[0150] A miRNA-141 detection kit comprises the electrochemical sensor prepared in Example 3, hairpin DNA H2, hairpin DNA H3, and TE buffer solution; wherein the nucleotide sequences of hairpin DNA H2 and hairpin DNA H3 are shown in SEQ ID NOs. 2-3.
[0151] The detection method of the kit is:
[0152] (1) Mix 10 μL H2 (10 μM) with 40 μL of the sample to be tested and incubate in a 37°C water bath for 30 min to obtain a mixed solution;
[0153] (2) Take 20 μL of the mixture, mix it with 20 μL of redox probe dispersion (i.e., H3 DNA, 10 μM) and 10 μL of TE buffer solution, vortex and drop 5 μL on the sensor surface, incubate at 37 °C for 1 h, and measure the DPV peak current value in 0.1 mM PBS with a pH of 7.4;
[0154] (3) Substitute the detected peak current into the standard curve Ip (nA) = 48.5 × LOG [C miRNA-141 , M]+977.3, the concentration of miRNA-141 in the sample was calculated.
[0155] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A high entropy alloy, characterized in that: The preparation method of the high entropy alloy comprises: (1) mixing NH4VO3, MnCl2, FeCl3, CrCl3 and HAuCl4 in a molar ratio of 1-2:1-2:1-2:1-2:0.2-0.8 and dissolving in water to obtain a metal salt solution; (2) mixing a solution of graphene quantum dots functionalized with arginine and folic acid and doped with boron and phosphorus with a metal salt solution to obtain a mixed solution; (3) The mixed solution is dried and thermally annealed to obtain a high entropy alloy.
2. The high entropy alloy according to claim 1, characterized in that The total concentration of the metal salt in the metal salt solution of step (1) is 1 to 4 mmol / L.
3. The high entropy alloy according to any one of claims 1 to 2, characterized in that: The mass ratio of the total mass of the metal salt in the mixed solution to the mass of the graphene quantum dots functionalized with arginine and folic acid and doped with boron and phosphorus is 1:1.2-1.8; The method for preparing arginine and folic acid functionalized, boron and phosphorus doped graphene quantum dots comprises: Dissolve citric acid, arginine, folic acid and boric acid in phosphoric acid according to a mass ratio of 1-3:1-2.7:0.063-1:0.7-1.3; heat at 150-180°C for 3-4 hours to obtain a crude product; redissolve the crude product, dialyze, and freeze-dry to obtain arginine and folic acid functionalized, boron and phosphorus doped graphene quantum dots; Optionally, the usage ratio of citric acid to phosphoric acid is 1-3 g: 0.2-0.4 mL.
4. The high entropy alloy according to any one of claims 1 to 3, characterized in that Thermal annealing includes two stages. The first stage is 1-5°C / min, heating to 380-420°C; the second stage is 5-8°C / min, heating to 880-920°C, and keeping warm for 2-3h.
5. A biosensor for detecting miRNA141, characterized in that: The preparation method of the biosensor comprises: The high entropy alloy and chitosan are mixed and added to the electrode surface to obtain a modified electrode; the H1 DNA solution is heated until the H1 DNA forms a hairpin structure to obtain a pretreated H1 solution; the pretreated H1 solution is mixed with a TCEP aqueous solution, added to the modified electrode surface, and incubated; mercaptoethanol is added to the electrode surface and incubated to obtain a biosensor for detecting miRNA141; H1 DNA has a methylene-thiol group connected to the 3' end of the nucleotide sequence shown in SEQ ID NO.1, that is: 5'-CCGAGATTCCAATGCCATAGTGTCTTCCAAGTTCAGATCTCAGACACTGTCTGGGTGTAAAGATGGGGACAGAATACAATAAG-(CH2)6-SH-3'; The preparation method of the high entropy alloy comprises: (1) mixing NH4VO3, MnCl2, FeCl3, CrCl3 and HAuCl4 in a molar ratio of 1-2:1-2:1-2:1-2:0.2-0.8 and dissolving in water to obtain a metal salt solution; (2) mixing the arginine and folic acid functionalized boron and phosphorus doped graphene quantum dot solution with the metal salt solution to obtain a mixed solution; (3) The mixed solution is dried and thermally annealed to obtain a high entropy alloy.
6. The biosensor according to claim 5, characterized in that The mass ratio of high entropy alloy to chitosan is 5-2:1-3; The mass ratio of the total mass of the metal salt to the mass ratio of the arginine and folic acid functionalized boron and phosphorus doped graphene quantum dots in the mixed solution of step (3) is 1:1.2-1.
8.
7. Use of the high entropy alloy according to any one of claims 1 to 4 or the biosensor according to any one of claims 5 to 6 in the preparation of a miRNA141 detection product; Optionally, the detection product includes a detection probe, a detection kit, and a detection device.
8. A kit for detecting miRNA141, characterized in that: The kit comprises the biosensor according to any one of claims 6 to 7, H2 DNA, and H3 DNA; Wherein, the nucleotide sequence of H2 DNA is shown as SEQ ID NO.2; H3 DNA is a ferrocene-modified hairpin DNA, and ferrocene FC is connected to the 5' end of the nucleotide sequence shown in SEQ ID NO.3, that is: 5'-FC-TCCTTGTTCTCATCTGAGCCATAGATTACACCCAGACAGTGTCTGAGATCTGAACTTGGAAGACAC-3'.
9. A method for detecting miRNA141, characterized in that: Using the biosensor according to any one of claims 5 to 6 or the kit according to claim 8, the detection method comprises: The H2 DNA solution and the H3 DNA solution are heated separately until a hairpin structure is formed; the H2 DNA solution and the sample to be tested are mixed and incubated to obtain a mixed solution; the mixed solution is mixed with the H3 DNA solution and the TE buffer solution to obtain a test solution, which is added to the surface of the biosensor and incubated; after incubation, the DPV curve is detected to obtain a peak current; the peak current is brought into the standard curve to calculate the miRNA-141 concentration; The standard curve is: Ip(nA)=48.5×LOG[C miRNA-141 , M]+977.3; where Ip is the peak current, nA; CmiRNA-141 is the concentration of miRNA141, M; Optionally, heating the H2 DNA solution and the H3 DNA solution to form a hairpin structure is performed by heating in a water bath at 90 to 95° C. for 4 to 6 minutes and cooling to room temperature; Optionally, the volume ratio of the H2 DNA solution to the sample to be tested is 8-10:40; 8-10; Optionally, 3 to 6 μL of the test solution is added to the surface of the biosensor; Optionally, the test solution is added to the biosensor surface and incubated at 35-37° C. for 1.5-2 h; Optionally, the concentration of the H2 DNA solution and the H3 DNA solution is 8-12 μM.
10. A method for improving the detection accuracy of miRNA141, characterized in that: Using the kit according to claim 8, the detection method comprises: Using the biosensor according to any one of claims 5 to 6 or the kit according to claim 8, the detection method comprises: The H2 DNA solution and the H3 DNA solution are heated separately until a hairpin structure is formed; the H2 DNA solution and the sample to be tested are mixed and incubated to obtain a mixed solution; the mixed solution is mixed with the H3 DNA solution and the TE buffer solution to obtain a test solution, which is added to the surface of the biosensor and incubated; after incubation, the DPV curve is detected to obtain a peak current; the peak current is brought into the standard curve to calculate the miRNA-141 concentration; The standard curve is: Ip(nA)=48.5×LOG[C miRNA-141 , M] + 977.3; where Ip (nA) is the peak current, C miRNA-141 is the concentration of miRNA141; Optionally, heating the H2 DNA solution and the H3 DNA solution to form a hairpin structure is performed by heating in a water bath at 90 to 95° C. for 4 to 6 minutes and cooling to room temperature; Optionally, the volume ratio of the H2 DNA solution to the sample to be tested is 8-10:40; 8-10; Optionally, 3 to 6 μL of the test solution is added to the surface of the biosensor; Optionally, the test solution is added to the biosensor surface and incubated at 35-37° C. for 1.5-2 h; Optionally, the concentration of the H2 DNA solution and the H3 DNA solution is 8-12 μM.